Development Strategy of Melayang Waterfall as a Sustainable Natural Tourism Attraction in Pejeng Kaja Village, Gianyar Regency - Arta, Dewa Gede Angga Parama; Suasapha, Anom Hery; Aridayanti, Dewa Ayu Nyoman (PT FORMOSA CENDEKIA GLOBAL, 2024)
Melayang Traditional Village is developing its natural tourism potential in the form of Melayang Waterfall, but the number of visitors is still low, with only around 12 to 20 tourists per day. Several promotional efforts have been made by the management, but the increase in visits has not been significant. Therefore, in-depth research is needed to formulate a strategy for sustainable tourism development. This study uses a qualitative method with primary and secondary data. Informants were selected through purposive sampling with a pentahelix approach. Data were collected through interviews with interview guide instruments, observations using checklists, documentation, and literature studies. Data analysis was carried out using the SWOT technique, through three stages: the input stage using the IFE and EFE matrices, the matching stage with the SWOT matrix, and the stage of determining priority strategies using the QSPM matrix analysis. From the SWOT analysis, 13 alternative strategies were generated, with five main strategies being further analyzed as priorities. These strategies include: 1) Inviting academics to provide training to the community on the positive impacts of tourism and tourism governance, 2) Establishing a management body to improve the quality of tourism services to be competitive, 3) Utilizing technology and social media as promotional tools, 4) Using local potential to compete with other tourist destinations, and 5) Utilizing the location to improve the community's economy.